Investigating How Consumer Susceptibility Moderates The Relationship Between Job Burnout, Ego Depletion, And Compulsive Buying Among Indonesian Migrant Workers - Randikaparsa, Irawan; Aryoko, Yudhistira Pradhipta; Firjatilah, Azalia Kumala (LP3M Universitas Putra Bangsa, 2024)
This research delves into the impact of job burnout on compulsive buying behavior within a group of 210 Indonesian domestic migrant workers in Taiwan. The study explores how ego depletion mediates this relationship and how consumer susceptibility to interpersonal influence moderates it. A survey method was used to collect data from participants, and the data were analyzed using structural equation modeling. The findings reveal that job burnout significantly heightens compulsive buying tendencies. However, ego depletion does not act as a mediating factor. On the contrary, consumer susceptibility to interpersonal influence plays a significant moderating role between ego depletion and compulsive buying, indicating that greater susceptibility weakens the impact of ego depletion on compulsive buying behavior. These results underscore the importance of addressing job burnout and considering interpersonal influences to mitigate compulsive buying behaviors among Indonesian domestic migrant workers in Taiwan, potentially enhancing their mental and financial well-being through targeted interventions.